Frequency-resolved photoconductivity studies in amorphous As-Se-Sb - Akat, E; Aktas, G (TAYLOR & FRANCIS LTD, 2001)
Frequency-resolved photocurrent measurements were carried out on amorphous As-Se-Sb films as a function of temperature (between 230 and 395K) and of excitation intensity (between 40 and 600 muW), yielding the lifetime distribution directly. Since the lifetime does depend on the excitation intensity, the results indicate that the recombination is through distant pairs, rather than by geminate (twin) pairs.
Keywords: DISTANT-PAIR RECOMBINATION; SI-H; SPECTROSCOPY; PHOTOCURRENT; KINETICS; Materials Science; Mechanics; Physics